2022
DOI: 10.36560/15820221579
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and medicinal plants: Challenges and strategies for production

Abstract: Medicinal plants, since antiquity, have been relevant due to their therapeutic properties, are widely used for the prevention and treatment of diseases. However, the growth and production of these plants are impacted by a notorious environmental stressor, salinity. In this sense, this study aimed to review the impacts of salinity on plant development, the deleterious effects of this environmental stressor on the production of medicinal plants, and the production strategies of these species in saline conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…This result indicated that P. nodiflora had a tolerance to high salinity and could be considered as a salt-tolerant plant that could become a useful plant material for studies on salt tolerance mechanisms [4]. In addition, it is proposed that salt-tolerant plants with potential uses for medicine, forage, essential oils, and biofuels can be developed for saline agriculture because the biomass reduction is not always proportional to their quality [22,23]. P. nodiflora aerial parts are mainly used for medicinal purposes in folk medicine and the pharmaceutical industry In addition, it is proposed that salt-tolerant plants with potential uses for medicine, forage, essential oils, and biofuels can be developed for saline agriculture because the biomass reduction is not always proportional to their quality [22,23].…”
Section: Effects Of Salinity On Biomass Of Shootsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated that P. nodiflora had a tolerance to high salinity and could be considered as a salt-tolerant plant that could become a useful plant material for studies on salt tolerance mechanisms [4]. In addition, it is proposed that salt-tolerant plants with potential uses for medicine, forage, essential oils, and biofuels can be developed for saline agriculture because the biomass reduction is not always proportional to their quality [22,23]. P. nodiflora aerial parts are mainly used for medicinal purposes in folk medicine and the pharmaceutical industry In addition, it is proposed that salt-tolerant plants with potential uses for medicine, forage, essential oils, and biofuels can be developed for saline agriculture because the biomass reduction is not always proportional to their quality [22,23].…”
Section: Effects Of Salinity On Biomass Of Shootsmentioning
confidence: 99%
“…In addition, it is proposed that salt-tolerant plants with potential uses for medicine, forage, essential oils, and biofuels can be developed for saline agriculture because the biomass reduction is not always proportional to their quality [22,23]. P. nodiflora aerial parts are mainly used for medicinal purposes in folk medicine and the pharmaceutical industry In addition, it is proposed that salt-tolerant plants with potential uses for medicine, forage, essential oils, and biofuels can be developed for saline agriculture because the biomass reduction is not always proportional to their quality [22,23]. P. nodiflora aerial parts are mainly used for medicinal purposes in folk medicine and the pharmaceutical industry [14].…”
Section: Effects Of Salinity On Biomass Of Shootsmentioning
confidence: 99%